A Simple Strategy for Glycosyltransferase‐Catalyzed Aminosugar Nucleotide Synthesis. Issue 5 (20th February 2014) - Zhang, Jianjun; Singh, Shanteri; Hughes, Ryan R.; Zhou, Maoquan; Sunkara, Manjula; Morris, Andrew J.; Thorson, Jon S.
Abstract A set of 2‐chloro‐4‐nitrophenyl glucosamino‐/xylosaminosides were synthesized and assessed as potential substrates in the context of glycosyltransferase‐catalyzed formation of the corresponding UDP/TDP‐α‐D‐glucosamino‐/xylosaminosugars and in single‐vessel model transglycosylation reactions. This study highlights a robust platform for aminosugar nucleotide synthesis and reveals OleD Loki to be a proficient catalyst for U/TDP‐aminosugar synthesis and utilization.